Antiangiogenic Nanomicelles for the Topical Delivery of Aflibercept to Treat Retinal Neovascular Disease. Issue 25 (2nd December 2021) - Zhao, Xinxin; Seah, Ivan; Xue, Kun; Wong, Wendy; Tan, Queenie Shu Woon; Ma, Xiaoxiao; Lin, Qianyu; Lim, Jason Y. C.; Liu, Zengping; Parikh, Bhav Harshad; Mehta, Karishma N.; Lai, Joel Weijia; et al.
Abstract: The traditional intravitreal injection delivery of antivascular endothelial growth factor (anti‐VEGF) to the posterior segment of the eye for treatment of retinal diseases is invasive and associated with sight‐threatening complications. To avoid such complications, there has been significant interest in developing polymers for topical drug delivery to the retina. This study reports a nanomicelle drug delivery system made of a copolymer EPC (nEPCs), which is capable of delivering aflibercept to the posterior segment topically through corneal–scleral routes. EPC is composed of poly(ethylene glycol) (PEG), poly(propylene glycol) (PPG), and polycaprolactone (PCL) segments. In this study, aflibercept‐loaded nEPCs (nEPCs + A) are capable of penetrating the cornea in ex vivo porcine eye models and deliver a clinically significant amount of aflibercept to the retina in laser‐induced choroidal neovascularization (CNV) murine models, causing CNV regression. nEPCs + A also demonstrate biocompatibility in vitro and in vivo. Interestingly, this study also suggests that nEPCs have intrinsic antiangiogenic properties. The ability to deliver anti‐VEGF drugs and the intrinsic antiangiogenic properties of nEPCs may result in synergistic effects, which can be harnessed for effective therapeutics. nEPCs may be a promising topical anti‐VEGF delivery platform for the treatment of retinal diseases. Abstract : nEPCs + A are aflibercept‐loaded nanomicelles formed by encapsulating aflibercept in an EPC copolymer solution. In this study, the ability of nEPCs + A to deliver clinically significant amounts of aflibercept to the retina for control of choroidal neovascularization in mice is described. Interestingly, nEPCs also demonstrate intrinsic antiangiogenic activity, which synergizes with their drug delivery capability for the treatment of neovascular retinal diseases.